2021
DOI: 10.1161/circulationaha.121.055176
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of Atrial Fibrillation Development in Patients With Embolic Stroke of Undetermined Source: An Analysis of the RE-SPECT ESUS Trial

Abstract: Background: A proportion of patients with embolic stroke of undetermined source (ESUS) have silent atrial fibrillation (AF) or develop AF after the initial evaluation. Better understanding of risk for development of AF is critical to implement optimal monitoring strategies with the goal of preventing recurrent stroke due to underlying AF. The RE-SPECT ESUS trial provides an opportunity to assess predictors for developing AF and associated recurrent stroke. Methods:… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
26
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(35 citation statements)
references
References 21 publications
4
26
0
1
Order By: Relevance
“…31 A recent analysis of the Randomized, Double-Blind, Evaluation in Secondary Stroke Prevention Comparing the Efficacy and Safety of the Oral Thrombin Inhibitor Dabigatran Etexilate Versus Acetylsalicylic Acid in Patients With Embolic Stroke of Undetermined Source (RE-SPECT ESUS) trial showed that a HAVOC score ≥3 was associated with a significantly higher possibility of incident atrial fibrillation compared with a score of 0 or 1 (HR: 2.68, 95% CI: 1.96-3.66). 38 Although an increase in the HAVOC score per 1 point was associated with an increased risk of atrial fibrillation (OR: 1.22, 95% CI:1.16-1.28), the score showed only modest ability to discriminate this risk (c-statistic: 0.62), 38 while the low rate of atrial fibrillation detection in patients with a low HAVOC score was not confirmed in external validation. 39 Similarly the recent Graz AF Risk Score developed among 150 patients with cryptogenic stroke showed good discriminating effect (AUC: 0.85, 95% CI 0.78-0.92).…”
Section: Candidates For Long-term Cardiac Monitoring: Look Hardermentioning
confidence: 99%
“…31 A recent analysis of the Randomized, Double-Blind, Evaluation in Secondary Stroke Prevention Comparing the Efficacy and Safety of the Oral Thrombin Inhibitor Dabigatran Etexilate Versus Acetylsalicylic Acid in Patients With Embolic Stroke of Undetermined Source (RE-SPECT ESUS) trial showed that a HAVOC score ≥3 was associated with a significantly higher possibility of incident atrial fibrillation compared with a score of 0 or 1 (HR: 2.68, 95% CI: 1.96-3.66). 38 Although an increase in the HAVOC score per 1 point was associated with an increased risk of atrial fibrillation (OR: 1.22, 95% CI:1.16-1.28), the score showed only modest ability to discriminate this risk (c-statistic: 0.62), 38 while the low rate of atrial fibrillation detection in patients with a low HAVOC score was not confirmed in external validation. 39 Similarly the recent Graz AF Risk Score developed among 150 patients with cryptogenic stroke showed good discriminating effect (AUC: 0.85, 95% CI 0.78-0.92).…”
Section: Candidates For Long-term Cardiac Monitoring: Look Hardermentioning
confidence: 99%
“…В исследовании Find-AF у пациентов с ИИ и значением NT-ProBNP > 240 пг/мл частота регистрации ФП при 7-дневном ХМ-ЭКГ составила 17,9% (по сравнению с 7,4% в группе с более низким уровнем NT-proBNP) [54]. При анализе данных RE-SPECT ESUS повышение NT-proBNP также было ассоциировано с выявлением ФП (ОР 1,74) [55]. Эксперты AF-SCREEN International Collaboration предлагают более высокий пороговый уровень натрийуретического пептида (400 пг/ мл) как предиктор выявления ФП после ИИ [31].…”
Section: клинический примерunclassified
“…Therefore, medical associations have stressed the importance of AF screening and current European guidelines recommend opportunistic screening of all adults > 65 years of age [ 1 ]. Nonetheless, many patients are diagnosed with AF only after a thromboembolic event has occurred [ 3 , 4 ]. Novel technologies such as machine learning may aid clinicians in identifying patients at a high risk of AF and may consequently improve patient outcome by reducing thromboembolic complications [ 5 ].…”
Section: Introductionmentioning
confidence: 99%